Corporate capital structure and how soft budget constraints may affect it - Marian Rizov (Journal of Economic Surveys, 2008)
This survey paper examines existing theories of capital structure and related empirical tests with the aim to derive theoretical as well empirically testable predictions about the implications of the soft budget constraint for corporate capital structure. We show that the soft budget constraint syndrome is relevant for a variety of institutional environments, from central planning to capi- talist economic systems, and consider features of company financing patterns in various institutional contexts. Special attention is paid to emerging and transition economies where, with the development of financial markets, companies reduce their financial dependence on the state and begin to borrow from a variety of sources. However, due to the persistence of soft budget constraints, corporate cap- ital structure in transition and emerging economies may still deviate significantly from the capital structure of companies operating under hard budget constraints.
Keywords: D02; E02; 330; Capital structure; Soft budget constraints; Transition economies; Emerging economies